FUNGSI KOMUNITAS SENI SEBAGAI PENGUATAN IDENTITAS, JARINGAN SOSIAL DAN PEMBERDAYAAN: Studi Kasus 'Komunitas Tanpa Nama' - Yobel Zefanya Sulu; Evelin J. R. Kawung; Antonius Purwanto (Journal Publicuho, 2024)
This research aims to find out the function of the Art Community as Identity Strengthening, Empowerment and Social Networking for its members. The research method uses qualitative with a phenomenological approach to find out the experiences of members of the 'Nameless Community'. Data collection through interviews, documentation and observation according to Sugiyono (2017). This research concludes that the art community is able to shape the identity of its members by providing a place to work, for example providing a stage to perform and publication media. Art members are empowered members as artists and are involved in preparing activities such as controlling the venue, and properties to be used, and directing the continuity of the event, also the Community provides opportunities for its members to be able to expand their network in each field of art so that there are several collaborations as well as mutual support between fellow members within the community and outside the community.